The Case Study Of The Dow Chemical Company - Lai, Kong Yong (2006)
The case study aims to share the success experience of Dow in its strategic management. The case study will start with PEST analysis on external environment in term of political, economies, social and technological changes and also industry competitive landscape through Michael Porter Five Forces Analysis.